2017
DOI: 10.1177/1179573517703342
|View full text |Cite
|
Sign up to set email alerts
|

Management of Viral Central Nervous System Infections: A Primer for Clinicians

Abstract: Viruses are a common cause of central nervous system (CNS) infections with many host, agent, and environmental factors influencing the expression of viral diseases. Viruses can be responsible for CNS disease through a variety of mechanisms including direct infection and replication within the CNS resulting in encephalitis, infection limited to the meninges, or immune-related processes such as acute disseminated encephalomyelitis. Common pathogens including herpes simplex virus, varicella zoster, and enteroviru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
67
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(72 citation statements)
references
References 100 publications
(196 reference statements)
4
67
0
1
Order By: Relevance
“…HSV-1 was found to be the causative agent in 24% of viral encephalitis patients (16/67 cases) in our study, which is in accordance with the previous reports (Granerod et al 2010;George et al 2014;Bookstaver et al 2017;López-Sánchez et al 2017). We also found that the patients with HSV-1 encephalitis were older than patients with non-HSV-1viral encephalitis; while 69% of patients with HSV-1 encephalitis were older than 50 years, this rate was 33% in patients with non-HSV-1 viral encephalitis.…”
Section: Discussionsupporting
confidence: 92%
“…HSV-1 was found to be the causative agent in 24% of viral encephalitis patients (16/67 cases) in our study, which is in accordance with the previous reports (Granerod et al 2010;George et al 2014;Bookstaver et al 2017;López-Sánchez et al 2017). We also found that the patients with HSV-1 encephalitis were older than patients with non-HSV-1viral encephalitis; while 69% of patients with HSV-1 encephalitis were older than 50 years, this rate was 33% in patients with non-HSV-1 viral encephalitis.…”
Section: Discussionsupporting
confidence: 92%
“…Including the few examples listed above, more than one hundred infectious agents (much of them being viruses) have been described as potentially encephalitogenic and an increasing number of positive viral identifications are now made with the help of modern molecular diagnostic methods [8,70,[108][109][110]. However, even after almost two decades into the 21st century and despite tremendous advances in clinical microbiology, the precise cause of CNS viral infections often remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…[61][62][63] In a year, ~10,000 patients suffer from encephalitis caused due to JE. 64,65 Prions causing…”
Section: • Acute Ve • Postinfectious Encephalomyelitis • Slow Viral Imentioning
confidence: 99%